Blessures chez des joueuses de basketball féminin de haut niveau durant une saison - Buffet, M.; Morel, N.; Navacchia, M.; Voyez, J.; Vella-Boucaud, J.; Edouard, P. (Science & Sports, 2015)
Aims: Women basketball has increased in competitiveness, and more contacts are currently experienced by players. The purpose of this study was to determine the incidence and characteristics of injuries within an elite woman's basketball team in France, in order to define preventive strategies. Materials and methods: In this prospective study over nine months, injuries have been defined and obtained according to the method developed by the International Olympic Committee. Results: The total incidence of injuries was 11.3/1000 h of exposure, with 8.3/1000 h of exposure during training and 144.0/1000 h of exposure during competition (48.3/1000 athletes-exposure). The lower limbs were most affected (58.9%) with thigh muscle lesions (13.7%) and ankle sprains (11.8%) being the most frequent. Contact injuries were the most frequent (33.3%). Fifty_one percent of injuries caused a time-loss, 73.1% of these injuries were minor (< 3 days), the time-loss mean was 10.8 ± 18.9 days per injury. Conclusion: This epidemiological study, which used a prospective and rigorous methodology, will allow us to determine preventive strategies for injuries, focused on the most frequent and/or most severe injuries. These preventive strategies could be isokinetic knee flexors and extensors evaluation, lower limb muscle strengthening of the lower limbs and ankle proprioception.